Iron ore pellets based-Ag2O nanoparticles as efficient Bi-functional heterogeneous catalyst for the synthesis tetrahydrobenzo[α]xanthens in green media - Faryabi, Ehsan; Sheikhhosseini, Enayatollah; Yahyazadehfar, Mahdieh (Frontiers in Chemistry, 2025)
Through the use of a microwave, iron ore pellets (IOP)-based Ag2O nanoparticles were successfully synthesized. They were then characterized by means of a vibrating sample magnetometer (VSM), Brunauer-Emmett-Teller (BET) surface area analysis, energy-dispersive X-ray (EDX) analysis, powder X-ray diffraction (XRD) analysis, EDX elemental mapping, and field emission scanning electron microscopy (FESEM). High quantities of tetrahydrobenzo[a]xanthen derivatives were obtained in a brief amount of time by the newly prepared nanocomposite, known as Ag2O NP@IOP, in a one-pot, three-component reaction involving different aryl aldehydes, naphthol, and dimedone. There is no appreciable loss of catalytic activity when the catalyst is recycled and utilized several times, and it can be easily retrieved using an external magnet. The reason for functionality of designed hybrid catalyst can be related to textural properties such as desirable specific surface area and significant porosity as well as the structural nature of the Ag2O NP@IOP catalyst.